FILSAFAT EKSISTENSIALISME JEAN-PAUL SARTRE - Mahmuddin Siregar (Institut agama islam negeri Padangsidimpuan, 2015)
Jean Paul-Sartre was born and raised in a society that is changing the way of thinking. Changes that covers all aspects of life and can not be controlled and supervised by anyone. This situation is compounded by the state of World War II so that the people of Europe are in a state of fear, oppressed and threatened. It is no wonder, when the Europeans are hypocritical to be able to save themselves. This is where Jean-Paul Sartre emerged with thoughts completely free both in doing meupun behave. He is promoting human liberty to do. However, the freedom of man is bound by other human freedom. Therefore, the presence of others restrict a person's freedom. Sartre Pemikiarn even deny the existence of God. Therefore, Sartre was one of the pioneers of the atheist philosophy.